"Take back control"? The effects of supranational integration on party-system polarization - Matakos, Konstantinos; Mutlu Eren, Hande; Konstantinidis, Nikitas (Springer, 2019)
In this paper, we examine the relationship between supranational integration and domestic party-system polarization (extremism). We first construct a theoretical argument that uncovers the key trade-off between the “output legitimacy” of a supranationally integrated party system and the inevitable loss of “input legitimacy” caused by externally imposed policy constraints. This translates into a strategic tradeoff between responsibility and responsiveness at the party level of electoral competition. We hypothesize that while moderate supranational policy constraints can initially speed-up platform convergence, ever-closer political integration may reverse the trend towards higher levels of party-system polarization and party extremism.We apply our framework to the case of EU integration and test our key non-monotonic prediction both at the party-system level of polarization and at the party level of ideological extremism. Finally, we apply to synthetic control method (SCM) for causal inference in comparative case studies to study how political integration and supranational policy constraints have affected their overall level of party-system polarization over time. Our overall empirical analysis strongly corroborates our theoretical argument.
Keywords: Party-system polarization;Extremism;Output legitimacy;Input legitimacy;European integration;Economic globalization;Supranational policy constraints;Synthetic control method; Party-system polarization; Extremism; Output legitimacy; Input legitimacy; European integration; Economic globalization; Supranational policy constraints; Synthetic control method; 59 Ciencia Política::5908 Teoría política; ODS 10 - Reducción de las desigualdades